From the public arena to the private arena: from Twitter to Telegram - Sanz-Martos, Sandra (Anuario ThinkEPI, 2023)
Social movements’ use of social networks is constantly evolving. From mobilizing people after the 11-M Madrid bombings through SMS to extremist groups’ mobilizing in November 2023 mainly through the application Telegram, content and the way organizing takes place have changed. What Twitter meant for the 15-M anti-austerity movement in Spain, serving as a true public arena, has little to do with social network activity today. There is hardly any space left for proposals, the exchange of ideas, and truthful information. While in 2004 there was talk of collective intelligence and crowd intelligence, in 2023 we are talking about disinformation and fake news. And the question is whether it is the type of platform or the nature of the movement that determines these changes in behavior.